Fuzzy Delphi method for project approach module in early science for children - Amiruddin, Nadia Shahira; Omar, Romarzila; Tazli, Uzzairah Nabila Ahmad; Abdullah, Norazilawati (Journal of Education and Learning (EduLearn), 2025)
This study focuses on designing a project-based learning module for early science education for home-based learning. The module comprises four dimensions: plants, planets, magnets and robotics, and weather. Using a quantitative approach and the design and development research (DDR) method, 15 early childhood education (ECE) experts were surveyed through a questionnaire with 20 items on a seven-point Likert scale. The Fuzzy Delphi method (FDM) with triangular Fuzzy numbers (TFN) was employed for data analysis, revealing a high level of expert consensus on the essential components of the module. The study achieved over 75% agreement, exceeding the threshold value (d) of 0.2 and α-cut of 0.5. Each dimension received favorable acceptance scores: plants (0.874), magnets and robotics (0.890), planets (0.918), and weather (0.903). The study emphasizes the acceptability of expert opinions on these dimensions, providing a valuable resource for early science education at home. The findings support addressing gaps in contributing to achieving sustainable development goal 4.2 by ensuring access to quality education for children.